Influência de borda sobre vegetação e microclima no cerrado paulista - Dodonov, Pavel (2011)
There is much variation in patterns of edge influence (EI) within a region due to factors such as vegetation structure, adjacent land use, orientation and edge contrast, and assessment of this variation is important for conservational planning. We studied EI on aspects of microclimate and vegetation in seven cerrado fragments in South-Eastern Brazil, sampling both savanna and forest vegetation. We located transects perpendicular to 14 cerrado edges adjacent to pastures, highways, sugarcane, silviculture, urban area, and forest roads. When significant, distance of EI varied from 15 to 80 m for temperature, 2 to 50 m for air moisture, 2 to 20 m for maximum vegetation height, 2 m for wind speed, 0 to 100 m for canopy cover, 0 to 20 m for exotic grass biomass, and 0 to 10 m for native grass biomass. The largest EI was observed in areas adjacent to pastures, but factors such as orientation, vegetations structure and land use were not sufficient to explain the observed variability. For conservation purposes, we recommend that buffers should be created between cerrado and the adjacent land use, especially in fragments adjacent to pastures and higways, in order to reduce EI.